Exploring the Antarctic aminopeptidase P from Pseudomonas sp. strain AMS3 through structural analysis and molecular dynamics simulation - Omar, Muhamad Nadzmi; Raja Abdul Rahman, Raja Noor Zaliha; Noor, Noor Dina Muhd; Latip, Wahhida; Knight, Victor Feizal; Mohamad Ali, Mohd Shukuri (Taylor and Francis, 2024)
Aminopeptidase P (APPro) is a crucial metalloaminopeptidase involved in amino acid cleavage from peptide N-termini, playing essential roles as versatile biocatalysts with applications ranging from pharmaceuticals to industrial processes. Despite acknowledging its potential for catalysis in lower temperatures, detailed molecular basis and biotechnological implications in cold environments are yet to be explored. Therefore, this research aims to investigate the molecular mechanisms underlying the cold-adapted characteristics of APPro from Pseudomonas sp. strain AMS3 (AMS3-APPro) through a detailed analysis of its structure and dynamics. In this study, structure analysis and molecular dynamics (MD) simulation of a predicted model of AMS3-APPro has been performed at different temperatures to assess structural flexibility and thermostability across a temperature range of 0–60 °C over 100 ns. The MD simulation results revealed that the structure were able to remain stable at low temperatures. Increased temperatures present a potential threat to the overall stability of AMS3-APPro by disrupting the intricate hydrogen bond networks crucial for maintaining structural integrity, thereby increasing the likelihood of protein unfolding. While the metal binding site at the catalytic core exhibits resilience at higher temperatures, highlighting its local structural integrity, the overall enzyme structure undergoes fluctuations and potential denaturation. This extensive structural instability surpasses the localized stability observed at the metal binding site. Consequently, these assessments offer in-depth understanding of the cold-adapted characteristics of AMS3-APPro, highlighting its capability to uphold its native conformation and stability in low-temperature environments. In summary, this research provides valuable insights into the cold-adapted features of AMS3-APPro, suggesting its efficient operation in low thermal conditions, particularly relevant for potential biotechnological applications in cold environments. Communicated by Ramaswamy H. Sarma. © 2024 Informa UK Limited, trading as Taylor & Francis Group.